Significance of L2 Lipase N-Terminal Residue in Maintaining Protein Integrity - Md. Jelas, Nur Hana (2010)
To understand the function of amino acid residue at lipase N-terminal end, substitution of the second amino acid in L2 lipase, Serine, to Phenylalanine was carried out. Phenylalanine is a very hydrophobic amino acid compared to Serine. Substituting amino acid of a protein with other amino acids that have opposite properties are known to cause major changes towards the characteristics of the protein if the residue holds an important function in the protein. General biochemical characteristics of mutated L2 lipase were studied and compared to the recombinant wild-type to determine the role of L2 lipase N-terminal residue. Mutated L2 lipase was created by extracting and purifying genomic DNA from thermophilic lipolytic Bacillus sp. L2. The purified genomic DNA was used as the template to amplify L2 lipase gene. Two degenerate primers, FT and RT were designed for the gene amplification. During the process, site-directed mutation of S2F was introduced at the N-terminal of the protein. The mutated gene was ligated into pTrcHis vector and cloned into Escherichia coli DH5 alpha. The recombinant gene was expressed using 0.0 5mM IPTG at the late log phase of cell growth stage, OD600nm ~0.75. The cell was harvested and lysed to obtain the expressed protein. The protein was purified using one step affinity chromatography. Recombinant wild-type L2 lipase worked optimally at 70°C while mutated L2 lipase showed only minute activity when assayed at 70°C. Instead, the mutant was found to be working optimally at 55°C. In addition, thermostability of mutated L2 lipase was also reduced to 45°C, compared to 60°C for wild-type when incubation was carried out for more than 60 min. The optimum pH for activity and stability of L2 lipase were also changed. Wild-type L2 lipase worked optimally and possessed highest stability at pH 9 while mutated L2 lipase worked optimally at pH 7 and maintained the best stability in solution with pH 10. Despite the decrease in thermostability and changes in optimum pH of the mutated L2 lipase, specific activity of the purified protein was found to be at 2043.14 U/mg. This is much higher compared to the recombinant wild-type which has a specific activity of 458 U/mg. Based on the nucleotide sequence of the wild-type L2 lipase, no other unintentional mutation had occurred within the newly cloned gene. Hereafter, any difference observed in the characteristics of the mutated L2 lipase which are different compared to the wild-type, it is deemed to be caused by the site-directed mutation of S2F. The effect of S2F mutation towards the biochemical characteristics of L2 lipase such as characteristics of the cofactor of the enzyme, substrate preferences, positional specificity, and the effect of surfactant and inhibitor towards the activity of the enzyme were studied to determine the potency of the mutation towards the general characteristics of the L2 lipase. It was later found that these properties were the same as the wild-type. Due to the similarity of the above properties, protein thermal melting analysis was carried out to verify the mutated L2 lipase structure integrity. The analysis confirmed the changes in L2 lipase thermostability. This study supports the theory that the point where the mutation happened has caused alteration of the surface of the proteins. The protein lost the integrity of its surface structure which caused the thermostability of the protein to change. The effect is also confirmed by the altered pH for optimum activity and stability of L2 lipase which occur due to the changes in the surface ionic charges of the protein. The loss however is seen to be compensated by the increase in the specific activity of the protein. Increase in L2 lipase specific activity by the mutation is however inconclusive. From this study, it was found that the ‘tail’ structure at the N-terminal residues of L2 lipase actually played a very important role in maintaining the integrity of the protein. Site-directed mutation at one site of the amino acids in the N-terminal residues results in a loss of protein integrity which is seen as a decrease in the protein thermostability. Interestingly, the loose protein structure seemed to allow the substrates to have an easier access to the active site of the protein which resulted in an increase in the specific activity of the protein.